1999
DOI: 10.1136/tc.8.3.306
|View full text |Cite
|
Sign up to set email alerts
|

Store tobacco policies: a survey of store managers, California, 1996-1997

Abstract: Objective-To identify store tobacco policies and retailer perception and beliefs that may have contributed to changes in compliance with youth access laws in California. Design-In the winter of 1996-7, a cross sectional, follow up telephone survey was conducted of California store managers whose stores were anonymously surveyed for illegal tobacco sales in the summer of 1996 (that is, 1996 Youth Tobacco Purchase Survey, YTPS). Conclusions-Store tobacco youth access policies, and managers' beliefs about the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The study also has several strengths. It is one of the only studies that includes tobacco retailer opinion about policies and links it to observations of retailer compliance [ 28 , 33 ] and the only one, thus far, which does so in relation to compliance with newer sales and marketing provisions of the Tobacco Control Act. It also uses theoretically derived factors that may influence policy implementation.…”
Section: Discussionmentioning
confidence: 99%
“…The study also has several strengths. It is one of the only studies that includes tobacco retailer opinion about policies and links it to observations of retailer compliance [ 28 , 33 ] and the only one, thus far, which does so in relation to compliance with newer sales and marketing provisions of the Tobacco Control Act. It also uses theoretically derived factors that may influence policy implementation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a lower likelihood of illegal sales rate was associated with chain stores compared with independent stores in California. 21 In another study, sales rates were highest in gas stations, 13 and a study in a metropolitan county in Washington State found that convenience stores selling gas were more likely to sell tobacco products to minors than restaurants, bars and tobacco discount stores. 15 Age-of-sale signs, asking about the purchaser's age, and requesting purchaser IDs were also associated with lower rates of underage sales.…”
Section: Introductionmentioning
confidence: 97%
“…Seventeen studies were conducted in the USA,6 14 17 23–36 three in Australia,37–39 two in the UK,8 15 two in South Korea7 40 and one each in Canada,41 New Zealand,42 and Indonesia 43. The earliest was published in 199114 and the most recent were published in 2020 17 25 38 39.…”
Section: Resultsmentioning
confidence: 99%
“…The most reported requirements described how tobacco products and advertising must be displayed in the store 6 7 14 15 17 23–26 28 29 32 34–40 42 43. For example, one retailer interviewed in the UK reported reserving two-thirds of their tobacco unit space for a contracted manufacturer15 and another in the USA recounted that manufacturer representatives required 45% of the tobacco retail space to be dedicated to that particular manufacturer 29.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation